EVALUASI TEBAL PERKERASAN LENTUR JALAN MENGGUNAKAN METODE ANALISA KOMPONEN (STUDI KASUS: PADA JALAN TEMINABUAN – AYAMARU KM 6+510 – KM 7+240) - Sigarlaki, Ester; Sukowati, Dwi Guntoro; Saputra, Asrul; Fajar, Muhammad Nur (Eternitas: Jurnal Teknik Sipil, 2024)
Roads are one of the most important infrastructures in carrying out economic activities, both accessibility and mobility of goods and services. As one of the connecting sections between districts which is also the main alternative section to go to the South Sorong Regent Office and Scholoo Keyen Hospital, the condition of the Teminabuan - Ayamaru Km 6 + 510 - Km 7 + 240 road has suffered severe damage such as cracks, bumpy roads, potholes and subsidence in the foundation layer. For this reason, it is necessary to repair roads. The method used in evaluating the thickness of bending pavement on the road is the Component Analysis method. This research method starts by collecting primary data and secondary data, namely CBR, LHR and rainfall data obtained directly from BMKG. Based on the results of analysis and calculations that have been carried out using the Component Analysis method on the Teminabuan - Ayamaru Km 6 + 510 - Km 7 + 240 road section, the thickness of each layer is obtained including the surface layer using Asphal Macadam with a thickness of 5 cm, the top foundation layer using 100% CBR Class A Crushed Stone with a thickness of 20 cm and the bottom foundation layer using 70% CBR Class A Sirtu with a thickness of 10 cm